Exploring individual character traits and behaviours of clinical academic allied health professionals: a qualitative study - Elizabeth King; Terry Cordrey; Owen Gustafson (BMC, 2023)
Abstract Background Clinical academic allied health professionals can positively impact patient care, organisational performance, and local research culture. Despite a previous national drive to increase these roles, they remain low in number with no clear strategy for growth. Reported barriers to this growth cite organisational and economic factors with little recognition of the challenges posed to individuals. There is a lack of research to help allied health professionals understand the personal challenges of clinical academic training and practice. The aim of this study is to explore the character traits and behaviours of clinical academic allied health professionals to understand the individual attributes and strategies taken to pursue a career in this field. Methods A semi-structured interview study design was used to collect data from aspiring and established clinical academic allied health professionals. Participants were recruited voluntarily through social media advertisement (aspiring) and purposively through direct email invitation (established). Participants were asked about their experience of pursuing a clinical academic career. The interviews were conducted virtually using Zoom and were audio recorded. The data were transcribed verbatim prior to reflexive thematic analysis. Informed consent was gained prior to data collection and the study was approved by the university's research ethics committee. Results Twenty participants from six allied health professions were interviewed. We developed five themes: risk and reward, don't wait to be invited, shifting motivations, research is a team sport, and staying the course. Clinical academic allied health professionals demonstrated traits including inquisitiveness, intuition, motivation, and resilience. The source of their motivation was rooted in improving clinical services, conducting research, and personal achievement. Conclusion Clinical academic allied health professionals describe personal traits of high inquisitiveness, opportunism, motivation, and determination in pursuing their career ambitions. The tolerance of rejection, failure, and risk was considered important and viewed as an essential source for learning and professional development. Future research should concentrate on ways to reduce the over-reliance on individual strength of character to succeed in this field and explore programmes to increase the preparedness and support for clinical academics from these professions.